2019
DOI: 10.4317/medoral.23088
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant peripheral giant cell lesions: report of 13 new cases and comparative histological and immunohistochemical analysis with peripheral and central giant cell lesions

Abstract: Background Few cases or peri-implant peripheral giant cell lesions (PGCL) have been reported in the literature. The aim of this study was to report 13 new cases of peri-implant PGCL and compare the expression of smooth muscle actin, Bcl-2 protein, GLUT-1, CD68, osteoprotegerin, receptor activator of nuclear factor kappa-B, Ki-67 and CD34 in these cases with PGCL and central giant cell lesions (CGCL). Material and Methods Clinical data were retrieved from the laboratory records and histological analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This could possibly be influenced by the fact that some professionals surgically remove the peri-implant tissues and do not send them for a histopathological study [ 13 ], or simply do not publish the cases. An interesting study, without conclusive results, found some differences in microvascular density, proliferative activity, and CD68 and Bcl-2 expression, between conventional and implant-associated granulomatous lesions [ 40 ]. In this study, histological and immunohistochemical aspects of peri-implant granulomatous lesions were analyzed and 13 new cases were presented, 2 in men and 11 in women.…”
Section: Discussionmentioning
confidence: 99%
“…This could possibly be influenced by the fact that some professionals surgically remove the peri-implant tissues and do not send them for a histopathological study [ 13 ], or simply do not publish the cases. An interesting study, without conclusive results, found some differences in microvascular density, proliferative activity, and CD68 and Bcl-2 expression, between conventional and implant-associated granulomatous lesions [ 40 ]. In this study, histological and immunohistochemical aspects of peri-implant granulomatous lesions were analyzed and 13 new cases were presented, 2 in men and 11 in women.…”
Section: Discussionmentioning
confidence: 99%
“…This wide range and high recurrence rate could be related both to incomplete removal of the lesions along with teeth or implants severely involved in the lesions and probably to the lack of screening of hormonal imbalances after certain histological diagnosis of PGCG is achieved. Histologically, PGCG not associated with PHPT are characterized by an increase of microvessel density and Bcl-2 and CD68 expressions [ 24 ] and mutations of KRAS and MAPK [ 25 ]. Nevertheless, further studies are necessary in order to understand if these findings are detectable in PGCG associated to PHPT too.…”
Section: Discussionmentioning
confidence: 99%
“…The development of computerized methods to analyze biopsies in order to make diagnostic and prognostic assessments, mainly based on cell morphology and architecture, is an open challenge (Irshad et al, 2014 ). The Aperio system 1 (Morais et al, 2019 ) is a commercial solution, which has been used in the immunohistochemical study of oral lesions, and offers solutions for slide glass scanning and automatic analysis of immunohistochemical staining. ImageJ (Rueden et al, 2017 ) is a freely accessible software that has also been used in the immunohistochemical study of oral lesions (Park et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%